Effects Of Information Education And Communication (IEC) -Based Intervention On Knowledge And Attitude Towards Cervical Cancer Preventionamong Teachers In Taraba State - Rimande-Joel, Rosethe; Obiechina, Georgy O. (Advances in Social Sciences Research Journal, 2020)
The Study Examined the Effect of Information Education and Communication (IEC)-Based Intervention on Knowledge and Attitude toward Cervical Cancer Prevention among Primary School Teachers in Jalingo, Taraba State. Pre-test and post-test quasi experimental design was adopted for the study. The study was guided by two specific objectives, two research questions and two null hypotheses tested at 0.05 alpha level. Population for the study consisted of (998) primary school female teachers in Jalingo. Multistage sampling procedure was used for recruiting (224) respondents; (111) for experimental group and (113) for the control group. Self-structured questionnaire titled knowledge and Attitude towards Cervical Cancer Prevention (KACCP) was used for data collection. Descriptive statistic of percentage and mean was used to analyze the demographic data and research questions, respectively; while inferential statistics of Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0. 05 alpha level. The compared result from the pretest and posttest showed that Information Education and Communication -Based intervention significantly increased knowledge, (F1, 213=65.626, p<.05) and positive attitude (F1, 213=368.367, p<.05) toward cervical cancer prevention. Based on the findings of the study it was recommended that periodic IEC-based programmes on cervical cancer should be organized for teachers and they be encouraged to step down the knowledge to pupils in order to spread knowledge and influence attitude and practice. Nigerian Ministry of health should develop and implement policy for IEC-based health education on cervical cancer prevention to be given in all maternal and child health clinics on each visit. And cervical cancer screening should be part of the routine examination.